Vote Buying in the US Congress - Ulrich Matter; Paolo Roberti; Michaela Slotwinski (Center for Economic Studies and ifo Institute (CESifo), 2019)
We assess the influence of moneyed interests on legislative decisions. Our theory predicts that the vote outcome distribution and donation flows in a legislature feature a discontinuity at the approval threshold of bills if special interest groups are involved in vote buying. Testing the theoretical predictions based on two decades of roll-call voting in the U.S. House, we identify the link between narrowly passed bills and well-timed campaign contributions. Several pieces of evidence substantiate our main finding, suggesting that moneyed interests exert remarkably effective control over the passage of contested bills.
Keywords: D72; D78; 330; legislative voting; campaign finance; special interest groups; lobbying; forensic economics